Transcutaneous Bilirubin Monitoring in Preterm Infants of 23 to 34 Weeks' Gestation - Weber, Jennifer; Vadasz-Chates, Nataly; Wade, Christine; Micetic, Becky; Gerkin, Richard; Rao, Suma (American Journal of Perinatology, 2021)
Objective The study aimed to evaluate the validity of transcutaneous bilirubin (TcB) measurements at three sites in premature infants born at 230/7 to 346/7 weeks' gestational age (GA) compared with total serum bilirubin (TSB) measurements.Study Design A prospective study was conducted at Banner – University Medical Center Phoenix, where informed consent was obtained from the infant's parent or legally authorized representative. Cohort A was comprised of infants 230/7 to 286/7 weeks' GA and Cohort B contained subjects 290/7 to 346/7 weeks' GA. Baseline TSB measurements were collected at approximately 24 hours of life, as the standard of care and the TcB measurements were obtained from the sternum, interscapular, and buttock areas at approximately ± 30 minutes from collection of the TSB. Statistical analysis of measurements including sensitivity, specificity, positive, and negative predictive values, and the area under the receiver operator characteristic curve (AUROC) were performed.Results A total of 166 infants were included in the study population. Cohort A consisted of 41 subjects and Cohort B contained 125 subjects. The results showed that baseline TcB measurements from the interscapular area were the most sensitive and specific with TSB levels >5.0 mg/dL in Cohort A. Baseline TcB measurements from the sternum demonstrated greatest sensitivity and specificity when the TSB level was >8.0 mg/dL in Cohort B. In general, each of the three sites in both cohorts demonstrated excellent AUROCs and negative predictive values.Conclusion The use of a TcB meter in preterm infants can be a reliable noninvasive screening tool for hyperbilirubinemia, and it may be beneficial in decreasing painful stimuli and iatrogenic blood loss when used as an adjunct to TSB monitoring.Key Points
Keywords: transcutaneous bilirubin; hyperbilirubinemia; prematurity; neonatal jaundice; neonatal intensive care